Fabrication and Properties of Tree-Branched Cellulose Nanofibers (CNFs) via Acid Hydrolysis Assisted with Pre-Disintegration Treatment - Jun Li; Dongyan Liu; Junsheng Li; Fei Yang; Guoxin Sui; Yu Dong (Nanomaterials, 2022)
In this paper, the novel morphology of cellulose nanofibers (CNFs) with a unique tree-branched structure was discovered by using acid hydrolysis assisted with pre-disintegration treatment from wood pulps. For comparison, the pulps derived from both softwood and hardwood were utilized to extract nanocellulose in order to validate the feasibility of proposed material fabrication technique. The morphology, crystalline structures, chemical structures, and thermal stability of nanocellulose were characterized by means of transmission electron microscopy (TEM), X-ray diffraction (XRD) analysis, Fourier transform infrared spectroscopy (FTIR), as well as thermogravimetric analysis (TGA). Prior to acid hydrolysis, softwood and hardwood pulps underwent the disintegration treatment in the fiber dissociator. It has been found that nanocellulose derived from disintegrated pulps possesses much longer fiber length (approximately 5–6 μm) and more evident tree-branched structures along with lower degree of crystallinity when compared with those untreated counterparts. The maximum mass loss rate of CNFs takes place at the temperature level of approximately 225 °C, and appears to be higher than that of cellulose nanowhiskers (CNWs), which might be attributed to an induced impact of amorphous content. On the other hand, disintegration treatment is quite beneficial to the enhancement of tensile strength of nanocellulose films. This study elaborates a new route of material fabrication toward the development of well-tailored tree-branched CNFs in order to broaden the potential widespread applications of nanocellulose with diverse morphological structures.